2016
DOI: 10.1016/j.atherosclerosis.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid interferon-γ receptor deficiency does not affect atherosclerosis in LDLR-/- mice

Abstract: Overall, our data argue against a role for myeloid IFNγR2 in atherosclerosis development. Since myeloid IFNγ signaling seems to be nonessential throughout atherogenesis, it is important to understand the mechanisms by which IFNγ acts in atherogenesis. In the future new studies should be performed considering other cell-specific targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…These findings suggest that the proatherogenic actions of IFNγ on macrophages may be independent of its canonical signaling pathway, which is supported by previous studies showing that myeloid cell deletion of Stat1 or Ifngr2 , two key components of this signaling pathway ( Ikushima et al, 2013 ), failed to attenuate atherogenesis ( Boshuizen et al, 2016 ; Lim et al, 2008 ). Consistent with this hypothesis, previous studies showed that IFNγ alters expression of many genes in Stat1 −/− macrophages ( Gil et al, 2001 ), suggesting that STAT1-independent mechanisms significantly contribute to the effects of this cytokine on macrophage gene expression and function.…”
Section: Discussionsupporting
confidence: 77%
“…These findings suggest that the proatherogenic actions of IFNγ on macrophages may be independent of its canonical signaling pathway, which is supported by previous studies showing that myeloid cell deletion of Stat1 or Ifngr2 , two key components of this signaling pathway ( Ikushima et al, 2013 ), failed to attenuate atherogenesis ( Boshuizen et al, 2016 ; Lim et al, 2008 ). Consistent with this hypothesis, previous studies showed that IFNγ alters expression of many genes in Stat1 −/− macrophages ( Gil et al, 2001 ), suggesting that STAT1-independent mechanisms significantly contribute to the effects of this cytokine on macrophage gene expression and function.…”
Section: Discussionsupporting
confidence: 77%
“…16 However, other reports suggest that myeloid IFNγ receptor 2 deficiency does not affect atherosclerosis in hyperlipidemic mice. 17 Such contradictory observations prompted us to examine the single-cell responses to IFNγ signaling in the atherosclerosis context. Several studies demonstrated that transcriptional heterogeneity and immune cell function may affect atherosclerosis outcomes.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Another macrophages population expressed canonical M1 (Cd11c, Ccl2 and Il-1β) or M2 (Mrc1, Clec10a and Mgl2) markers. Surprisingly, there are more expression M2-marker resident macrophage populations in the plaque in comparison to M1-marker populations, maybe due to low IL-4 and IL-13 levels in the plaque [ 42 ], but not associated with IFN-γ and its receptor [ 43 ]. This phenomenon is very interesting, because anti-inflammation therapy, such as CANTOS clinical trial, using anti-IL-1β antibody-canakinumab, significantly reduced recurrent cardiovascular events independent of lipid-lowering [ 44 ].…”
Section: Intraplaque Cell Types and Interactions In Plaque Stabilitymentioning
confidence: 99%